Pelletized Mucuna pruriens (L) DC. and Trichoderma harzianum Rifai applied on tomato (Solanum lycopersicum L.) as an amendment and biocontrol agent - Martínez-Alfaro, Arnaldo (2024)
Introduction. In organic agriculture, green manures and biocontrols are used as methods for fertilization and pest control. However, their independent application of these inputs increases production costs. A pelletized formulation is proposed to allow simultaneous application of both inputs. Objective. To evaluate the effect of pelletized Mucuna pruriens (L.) DC. inoculated with Trichoderma harzianum Rifai on nutritional intake, agricultural yield, and regulation of Fusarium oxysporum f. sp. lycopersici in tomato (Solanum lycopersicum L.). Materials and methods. The experiment was carried out in 2022 in Tablón del Guarco, Cartago, Costa Rica, using a randomized complete block design with seven treatments and seven repetitions. Two formulations (A and B) of biopellet (M. pruriens + zeolite + T. harzianum) were applied at three dosages (15, 30, 50 g/plant). T. harzianum was added at a rate of 5 g/kg of biopellet. Applications of each treatment were conducted every 15 days for a total of eight applications. At the time of planting, F. oxysporum was inoculated (100 mL/plant with a concentration of 1 x 103 CFU). Results. The application of biopellet achieved a yield and weight of high-quality fruits similar to the commercial control. There were no significant differences among treatments for second and third-quality fruits. The technical efficiency in controlling F. oxysporum reached 97.6 % with biopellet. This amendment increased the levels of Carbon (C), Nitrogen (N), and organic matter in the soil and affected the nutritional content of the plant foliage in the first 60 days after sowing. Conclusions. The biopellet has the capacity to make chemical and organic contributions to the soil, which improves the nutrition of the tomato crop. It could be also a biocontrol alternative against F. oxysporum and compatible with T. harzianum.